KECEMASAN MENGHADAPI DUNIA KERJA PADA MAHASISWA TINGKAT AKHIR DI UNIKA SOEGIJAPRANATA DITINJAU DARI HUBUNGAN KEAKTIFAN MENGIKUTI ORGANISASI - Brigitan Argasiam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2022)
The purpose of this study was to find out empirically the relationship between active participation in organizations in final year students facing the world of work at Soegijapranata Unika. The hypothesis in this study is a negative relationship between anxiety facing the world of work with active participation in organizations at the final student level at Soegijapranata Unika. The subjects of this study were final year students of Unika Soegijapranta Semarang who were working on their final project. The sampling technique in this study was purposive sampling. Data collection in this study used an anxiety scale to face the world of work with active participation in the organization. The subjects were 50 final year students. The research was conducted using quantitative methods. Based on the analysis of the product moment correlation data, the correlation coefficient value is rxy = 0.445 with (p < 0.01). This shows that it means that there is a very significant negative relationship between anxiety in facing the world of work and active participation in student-level organizations at the final Soegija Unika. The higher the activeness in participating in the Soegijapranata Unika student organization, the lower the face of the world of work and the lower the active participation in the Soegijapranata Unika student organization, the higher the anxiety in the world of work. The effective contribution of the variable of active participation in the organization for final year students to face the world of work is 19.8%.